Strengthen Discipline Through Civic Education to Face the Industry 4.0 - Putri Saylendra, Nadya; Susanto, Erwin; Komala Putri, Ratna (International Journal of Psychosocial Rehabilitation, 2020)
This article is motivated by the introduction of the term industry 4.0 in 2011. Since then, the trend of automation and data exchange has become a global phenomenon. The impact of the industry 4.0 was felt especially in Karawang Regency, since Karawang was made the center of an international standard industry, of course the exchange of data and information was also getting faster so that the demands of high school graduates ready to work in Karawang were so great. In the context of schooling, Pancasila and Civic Education as character education is tasked with strengthening character values, so that it is expected to strengthen the values of discipline character that every student must have to face the industry 4.0. This article aims to describe Pancasila and Civic Education to strengthen discipline characters of high school students in Karawang to face the industry 4.0. The approach taken in this study is the survey method and correlation. The results of this study is significantly Pancasila and Citizenship Education is able to strengthen the discipline character of high school students in Karawang regency to face industry 4.0.